Factors associated with suicide ideation in patients of a Peruvian Hospital: Factores de riesgo asociados a ideación suicida en pacientes de un Hospital del Perú - Chavez-Cáceres, Rosa (2020)
Introduction: Suicide manifests itself through multiple behaviors, it begins with suicidal ideationand ends with suicide. Objective: To demonstrate the risk factors associated with suicidal ideation inpatients with depression cared for in a level III-2 hospital in Peru. Methods: Observational, analytical,cross-sectional study, with a quantitative approach. Sampling was non-probabilistic for convenience; thesample was made up of 201 patients attended by an external psychiatric clinic of the María Auxiliadorahospital, from January to February 2020. The survey technique, a data collection form and the adaptedBeck scale instrument were used. Results: Of the 201 patients, 46 (22.9%) had suicidal ideation, of them,25 (54.3%) were young, female 27 (58.7%), had no partner 27 (58.6 %), 32 (69.7%) were born in Lima,received treatment for more than one year 43 (93.5%), had a regular to poor family relationship 42 (91.3%)and consumed alcohol 33 (71.7%), tobacco 26 (56.5%) and drugs16 (34.8%). The risk factors associatedwith suicidal ideation in the bivariate analysis were young age, male sex, place of birth Lima, maritalstatus without a partner, treatment time greater than one year and consumption of alcohol, tobaccoand drugs (95% CI, p <0.005); and in the multivariate analysis it was only associated with drug use (OR:11.31 CI 2.05-62.46 p <0.005). Conclusion: Drug use is associated with suicidal ideation in patients seenin a level III-2 hospital.